Enantioseparations of polyhalogenated 4, 4'‐bipyridines on polysaccharide‐based chiral stationary phases and molecular dynamics simulations of selector–selectand interactions. Issue 17 (21st April 2021) - Dallocchio, Roberto; Sechi, Barbara; Dessì, Alessandro; Chankvetadze, Bezhan; Cossu, Sergio; Mamane, Victor; Weiss, Robin; Pale, Patrick; Peluso, Paola
Abstract: 2'‐(4‐Pyridyl)‐ and 2'‐(4‐hydroxyphenyl)‐TCIBPs (TCIBP = 3, 3', 5, 5'‐tetrachloro‐2‐iodo‐4, 4'‐bipyridyl) are chiral compounds that showed interesting inhibition activity against transthyretin fibrillation in vitro . We became interested in their enantioseparation since we noticed that the M ‐stereoisomer is more effective than the P ‐enantiomer. Based thereon, we recently reported the enantioseparation of 2'‐substituted TCIBP derivatives with amylose‐based chiral columns. Following this study, herein we describe the comparative enantioseparation of both 2'‐(4‐pyridyl)‐ and 2'‐(4‐hydroxyphenyl)‐TCIBPs on four cellulose phenylcarbamate‐based chiral columns aiming to explore the effect of the polymer backbone, as well as the nature and position of substituents on the side groups on the enantioseparability of these compounds. In the frame of this project, the impact of subtle variations of analyte and polysaccharide structures, and mobile phase (MP) polarity on retention and selectivity was evaluated. The effect of temperature on retention and selectivity was also considered, and overall thermodynamic parameters associated with the analyte adsorption onto the CSP surface were derived from van 't Hoff plots. Interesting cases of enantiomer elution order (EEO) reversal were observed. In particular, the EEO was shown to be dependent on polysaccharide backbone, the elution sequence of the two analytes being P ‐ M and M ‐ P on cellulose and amylose tris (3, 5‐dimethylphenylcarbamate), respectively. In this regard, a theoretical investigation based on molecular dynamics (MD) simulations was performed by using amylose and cellulose tris (3, 5‐dimethylphenylcarbamate) nonamers as virtual models of the polysaccharide‐based selectors. This exploration at the molecular level shed light on the origin of the enantiodiscrimination processes.